Statistical analysis of 484 Mycobacterium tuberculosis genomes reveals an association between single nucleotide polymorphisms on ponA1 gene and LAM and Haarlem lineages - Jhonatan Rabanal (Asociación Colombiana de Infectología, 2021)
Objectives: Evaluate the association between rifampicin resistance and the presence of at least one SNP in the rpoB and ponA1 genes and the spoligotype defined lineages. Material and Methods: This study analyzed two databases of 484 genomes of M. tuberculosis from strains isolated from patients in the cities of Lima and Callao, for which the odds ratio (OR) was calculated considering belonging to a certain spoligotype defined lineages as an exposure factor. Results: No statistically significant association (ρ value> 0.05) was found between the presence of at least one SNP in the rpoB gene and the lineages included in the study (LAM, Haarlem, T and Beijing). However, a statistically significant association was found between the presence of at least one SNP in the ponA1 gene and the LAM and Haarlem lineages (ρ value <0.05). An association was found between the P631S SNP in the ponA1 gene and the LAM and Haarlem lineages; and the A516T SNP, of this same gene, presented an association with the LAM lineage. Likewise, an association was found between rifampicin resistance and the LAM lineage. Conclusions: The presence of SNPs in the ponA1 gene is associated with the LAM and Haarlem lineages.